2010
DOI: 10.4141/cjps09174
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and abundance of an allergenic weed, common ragweed (Ambrosia artemisiifolia L.), in rural settings of southern Quebec, Canada

Abstract: . 2010. Distribution and abundance of an allergenic weed, common ragweed (Ambrosia artemisiifolia L.), in rural settings of southern Que´bec, Canada. Can. J. Plant Sci. 90: 549{557. Common ragweed (Ambrosia artemisiifolia L.) is an important weed of urban and rural settings in eastern Canada. Where the species is abundant, its wind-dispersed pollen is responsible for most cases of allergic rhinitis or ''hayfever'' in August and September. Despite its adverse health effects, there is little information on the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…This conclusion validates the hypothesis that a spectral proximity between Common Ragweed in urban settings and Common Ragweed in agricultural settings exists within the green band (500-590 nm). This conclusion is sustained by the results of Nádor et al [14] and Simard and Benoit [7] in rural settings. The response curve of Common Ragweed in Montreal (WV2) is very similar to that of the study conducted by Nádor et al [15] in rural cultivated fields in Hungary and also using WV2 imagery.…”
Section: A High Spectral Confusion In Varying Geographic Conditionssupporting
confidence: 60%
See 3 more Smart Citations
“…This conclusion validates the hypothesis that a spectral proximity between Common Ragweed in urban settings and Common Ragweed in agricultural settings exists within the green band (500-590 nm). This conclusion is sustained by the results of Nádor et al [14] and Simard and Benoit [7] in rural settings. The response curve of Common Ragweed in Montreal (WV2) is very similar to that of the study conducted by Nádor et al [15] in rural cultivated fields in Hungary and also using WV2 imagery.…”
Section: A High Spectral Confusion In Varying Geographic Conditionssupporting
confidence: 60%
“…However, at the opposite of the present study their inquiries revealed the importance of the Yellow band (585-625 nm). Simard and Benoit [7] studied the distribution of Common Ragweed in the rural areas of Valleyfield; they concluded that the density of Common Ragweed was higher by paved roads than by cultivated fields and inside the fields themselves. Their study was conducted at the same period of the present one (summer 2009).…”
Section: A High Spectral Confusion In Varying Geographic Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Attempted control of Ambrosia artemisiifolia has employed a range of physical, chemical and biological management techniques [19] that might also be combined. Ambrosia artemisiifolia tolerates substantial physical damage such as removal of the stem apex and leaves, because the plants regenerate from buds from the base or increase growth of existing lateral stems [30][31][32][33]. Cutting of vegetative plants is reported to delay the initiation of flowering but does not prevent reproduction [31], whereas hand pulling is reported to be most effective but very laborious [34,35].…”
mentioning
confidence: 99%